2023
DOI: 10.1083/jcb.202111069
|View full text |Cite
|
Sign up to set email alerts
|

The C10orf76–PI4KB axis orchestrates CERT-mediated ceramide trafficking to the distal Golgi

Abstract: Phosphatidylinositol 4-monophosphate [PtdIns(4)P] is a precursor for various phosphoinositides but also a membrane-embedded component crucial for membrane contact sites (MCSs). Several lipid transfer proteins are recruited to MCSs by recognizing PtdIns(4)P; however, it remains poorly elucidated how the production of PtdIns(4)P for lipid transport at MCSs is regulated. Following human genome-wide screening, we discovered that the PtdIns(4)P-related genes PI4KB, ACBD3, and C10orf76 are involved in endoplasmic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 101 publications
1
12
0
Order By: Relevance
“…The ceramide transport protein (CERT) plays a critical role in the intracellular transportation of ceramides from the ER to the Golgi in mammals. This cytosolic protein, with a size of 68 kDa, functions by collecting newly synthesized ceramides at the ER and facilitating their transfer to the trans-Golgi ( Hanada et al, 2003 ; Kawano et al, 2006 ; Mizuike et al, 2023 ). CERT encompasses various functional domains and motifs, similar to other lipid transfer proteins (LTPs).…”
Section: Ceramide Transfer Proteins In Mammalian Cellsmentioning
confidence: 99%
“…The ceramide transport protein (CERT) plays a critical role in the intracellular transportation of ceramides from the ER to the Golgi in mammals. This cytosolic protein, with a size of 68 kDa, functions by collecting newly synthesized ceramides at the ER and facilitating their transfer to the trans-Golgi ( Hanada et al, 2003 ; Kawano et al, 2006 ; Mizuike et al, 2023 ). CERT encompasses various functional domains and motifs, similar to other lipid transfer proteins (LTPs).…”
Section: Ceramide Transfer Proteins In Mammalian Cellsmentioning
confidence: 99%
“…A pool of PtdIns(4)P generated by the DGARM–PI4KB axis was shown to be important for defining the site at which CERT works to provide ceramide for sphingomyelin synthesis ( Mizuike et al, 2023 ), as discussed above. In this study, ACBD3 was also indicated to partially compensate for this function.…”
Section: Introductionmentioning
confidence: 98%
“…Phosphatidylinositol 4-monophosphate (PtdIns(4)P) is a well-studied membrane component for its role in specifying various contact sites. We recently found that C10orf76 (alias ARMH3), a PtdIns 4-kinase-binding protein, is recruited to the distal Golgi and plays a pivotal role in the ER-to-distal Golgi trafficking of ceramide for the synthesis of sphingomyelin ( Mizuike et al, 2023 ). Together with the predicted structure of C10orf76 as an armadillo (ARM)-like fold ( Figure 1 ), consisting of α-helices arranged into a characteristic superhelix ( Tewari et al, 2010 ), we proposed to rename it to DGARM after a d istal G olgi arm adillo repeat protein.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations